PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI AKADEMIK PADA ASRAMA BAHASA MENGGUNAKAN TOGAF - Akhlis Munazilin; Milka Afifah; Wulan Shelfiana Kamil (CV. Denasya Smart Publisher, 2025)
The rapid advancement of information technology requires educational institutions to implement academic management systems that are structured, integrated, and aligned with organizational needs. The Language Dormitory of Pondok Pesantren Salafiyah Syafi’iyah Sukorejo, as a non-formal educational institution, continues to face challenges in academic management, which is predominantly conducted manually, leading to inefficiencies, data duplication, and delays in information delivery. This study aims to design an enterprise architecture for the academic information system at the Language Dormitory using the TOGAF (The Open Group Architecture Framework). The research methodology includes a literature review, field observations, and interviews with relevant stakeholders, which are subsequently analyzed through the TOGAF ADM phases. The results produce an enterprise architecture design encompassing business architecture, application architecture, and data architecture tailored to the academic processes of the language dormitory. The proposed architecture recommends the development of an integrated academic information system to support student registration, learning activities, academic evaluation, and reporting processes. This enterprise architecture design is expected to serve as a strategic guideline for sustainable academic information system development and to enhance the effectiveness and quality of academic services at the Language Dormitory.